2013
DOI: 10.17221/6711-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary arginine supplementation on reproductive performance and immunity of sows

Abstract: Arginine (Arg) is considered to have beneficial effects on placental development and function, as well as reproductive performance. The well-developed placenta is highly required in late gestation for rapid fetal growth, however, it is unknown if there is a crucial role of Arg in late gestation. Likewise, the immunological response of sows to Arg needs to be determined. Therefore, this study is designed to investigate the effects of dietary Arg supplementation on reproductive performance and immunity of sows. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 34 publications
7
36
0
Order By: Relevance
“…Dallanora et al () reported a decrease in the number of low‐weight piglets, with a significant decrease in the number of piglets weighing less than 1,000 g from sows supplemented with 1.0% L‐arginine in the middle third of gestation. Nuntapaitoon et al () supplemented the diets of sows with 0.5% L‐arginine in the final third of gestation and observed a decreased incidence of piglets weighing less than 1,000 g and an increased number of piglets weighing >1,350 g. A decrease (4%) in the number of piglets weighing less than 1,000 g was also reported after dietary L‐arginine supplementation in sows from 30 to 114 days of gestation (Che et al, ). These studies indicate that L‐arginine supplementation at the end of gestation may effectively modulate piglet birthweights (Nuntapaitoon et al, ) and determine which gestational nutritional strategies may selectively improve foetal development and growth, thereby favouring low‐weight piglets (Dwyer, Stickland, & Fletcher, ; Quesnel et al, ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Dallanora et al () reported a decrease in the number of low‐weight piglets, with a significant decrease in the number of piglets weighing less than 1,000 g from sows supplemented with 1.0% L‐arginine in the middle third of gestation. Nuntapaitoon et al () supplemented the diets of sows with 0.5% L‐arginine in the final third of gestation and observed a decreased incidence of piglets weighing less than 1,000 g and an increased number of piglets weighing >1,350 g. A decrease (4%) in the number of piglets weighing less than 1,000 g was also reported after dietary L‐arginine supplementation in sows from 30 to 114 days of gestation (Che et al, ). These studies indicate that L‐arginine supplementation at the end of gestation may effectively modulate piglet birthweights (Nuntapaitoon et al, ) and determine which gestational nutritional strategies may selectively improve foetal development and growth, thereby favouring low‐weight piglets (Dwyer, Stickland, & Fletcher, ; Quesnel et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…L‐arginine supplementation at 0.5% in the last third of gestation increased piglet birthweights by approximately 100 g, thus suggesting increased placental blood flow and improved foetal development compared with non‐supplemented sows (Nuntapaitoon, Muns, Theil, & Tummaruk, ). Studies have also reported improved litter uniformity after amino acid supplementation (Che et al, ). Some studies found results similar to the results herein, observing no supplementation effect on piglet birthweight (Bass et al, ; Quesnel et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…; Che et al. ). So, the improved litter performance in response to supplemental NCG in the diet can be attributed to production of arginine.…”
Section: Discussionmentioning
confidence: 97%
“…; Che et al. ). Because total nitrogen and amino acid accretion in the foetal pig increased progressively from days 60 to 114 of gestation, so the delivery of amino acids from uterine and placentae to foetal pig must increase with advancing gestation (Wu et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation